ПРАКТИЧНА РЕАЛІЗАЦІЯ ІННОВАЦІЙНИХ ПІДХОДІВ ДО РОЗВИТКУ МОВЛЕННЯ ДІТЕЙ ІЗ ОСОБЛИВИМИ ОСВІТНІМИ ПОТРЕБАМИ В УМОВАХ ІНКЛЮЗІЇ ЗАСОБАМИ УКРАЇНСЬКОЇ ВИШИВАНКИ - Leniv, Zoriana (Mountain School of Ukrainian Carpaty, 2020)
In this article the main aspects of embroidery in inclusive education of children with special educational needs (SEN) are considered: 1) cultural and educational; 2) professional rehabilitational; 3) therapeutic educational. It is disclosed in details the third aspect which is implemented through studying Ukrainian embroideries (vyshivanka): types of ornaments, embroidery techniques, colors, symbols, regional features, etc. The main attention is focused on practical use of embroideries for the purpose of formation of prerequisites to the development of a written language of younger schoolchildren with special educational needs in the New Ukrainian school. Now there is a revaluation of values, overcoming the settled stereotypes, medical, defectological rudiments on the education of people with special educational needs, including children, which becomes the basis of a new legal, scientific and methodological, organizational and substantive support for their education. However, if the normative-legal component of this process is currently sufficiently developed in Ukraine, the scientific-methodical and organizational-substantive components still require significant theoretical-experimental research and practical development, that determine the relevance of finding innovative ways of practical implementation of inclusive education. As a result of the analysis of scientific works of scientists it was found that among the main principles of development of national education is the definition of directions and means of its transformation into the social elevator of a world sample. Awareness of importance of realization the outlined bases in practice stimulates the development of new non-standard approaches to development of children with SEN in terms of inclusion, including the formation of speech by samples of Ukrainian embroideries, which allows to combine this process with national-patriotic education. Therefore, the interdisciplinary research is based on the advanced achievements of foreign and domestic science and practice in the field of inclusion, as well as logopedics based on a neuropsychological approach to understand the functioning of written language. In fragments from an author's methodical system game techniques, tasks, exercises for development of the highest mental processes, grapho-motor skills, optical-spatial orientation, components of a speech system are presented. Phonetic-phonemic processes, lexical-grammatical structure and coherent speech can be integrated both into the system of correctional-developmental classes of a speech therapist and into the work of a teacher and a teacher's assistant at the lessons within inclusive classroom. The prospects of a research consist of development and application of elements of the methodology in high school, and also its approbation at the Ukrainian schools of diaspora for the purpose of studying the native language.